(untitled) (Indian Journal of Animal Production and Management, 2015)
The data pertaining to Holstein Friesian x Gir halfbreds were collected on first lactation traits and classified according to generation, period of birth/calving, season of birth/calving and peak milk yield and analyzed by least squares method. Corrected data were used for estimation of genetic and phenotypic correlation and heritability. The economic weights of different traits were calculated. The relative economic value of Genetic improvement of Holstein Friesian x Gir halfbreds different traits was obtained by considering the economic weight of FLMY as standard unit. The aggregate genetic economic gain (“H) and relative efficiency of the index was computed. Selection indices (21) were constructed by using different traits in different combinations. Index with four trait combination I5 [(-1.504)(AFC) + (0.337)(FLMY) + (- 6.840) (FLL) + (2.412) (FCI)] and index with three trait combination I2 [(-1.305) (AFC) + (1.854) (FDP) + (-0.055) (FLMY)] were found to be the most useful indices. Using I5 index the response in each trait per generation was expected to be decrease in age at first calving (228.80 days), increase in first lactation milk yield (521.04 kg), decrease in first lactation length (50.31 days) and decrease in first calving interval (42.50 days). While using I2 index response in each trait per generation was expected to be 188.54 days in age at first calving (AFC), 10.22 days in first dry period (FDP) and 73.39 kg in first lactation milk yield (FLMY). Therefore, form these results it may be inferred that out of 21 selection indices constructed for HF x Gir halfbreds, index I5 from four traits combination and I2 from three traits combination were found to be relatively efficient indices and rated as the most useful indices for their high reliability and expected genetic gain.